Iron age decorative metalwork in southern Africa: an archival study - Walker, Ellen Jeanine (Department of Archaeology, 2016)
This thesis addresses continuity and change in the manufacture and use of decorative metalwork in the Iron Age (200-1900 AD) of southern Africa, within a framework of archival studies and artefact studies theory. The thesis adopted a direct historical approach which exploited the huge database of existing information to create typologies of objects and processing techniques that are prominent in ethno-historical sources of the 19th and 20th centuries. This process enabled for the first time, a comprehensive mapping of object typologies and techniques of manufacture by ethnic groups thereby allowing cross cultural comparisons. Subsequently, the study explored the typology of objects utilized further back in the time of the Early Iron Age using archaeological evidence. It demonstrated that most of the objects used in the Iron Age were similar to those that were used in the 19th century. However, new innovations were made along the way with metals and alloys being constantly added to the range of materials worked. A dedicated visual study of fabrication techniques employed in the manufacture of ethnographic materials housed at Iziko Museum of Cape Town was carried out. The techniques gleaned from the macroscopic study were compared with those metallographically documented in the literature for the manufacture of Iron Age objects, further exposing continuity and change in metal fabrication. The social, economic and political role of decorative metalwork was hardly static, and varied from context to context and group to group.